2018
DOI: 10.1186/s13223-018-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunotherapy induces alterations in monocytes and dendritic cells homeostasis in allergic rhinitis patients

Abstract: BackgroundSpecific subcutaneous immunotherapy (SCIT) can achieve long-term remission in patients with allergic rhinitis (AR) through complex and still unknown mechanisms. The aim of this study is to evaluate the effect of SCIT over CD16+ and CD16− monocytes, myeloid (mDCs) and plasmacytoid dendritic cells (pDCs) in patients with AR, comparatively to pharmacological standard treatment (non-SIT).MethodsThe relative frequency and absolute number of monocytes and DC subsets, the frequency of these cells producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…It is known that in individuals suffering from hymenoptera venom allergy, numeric and phenotypic changes in blood pDC are occurring during allergen-specific immunotherapy [ 63 ]. These findings are in line with the observation of a decrease of circulating pDC and phenotypic changes in patients with HDM allergy during subcutaneous immunotherapy [ 64 ]. Furthermore, it has been described that pDC are generally critical for tolerance induction by inducing Treg cells in a mouse model for uptake and presentation of oral allergen OVA [ 65 ].…”
Section: Discussionsupporting
confidence: 89%
“…It is known that in individuals suffering from hymenoptera venom allergy, numeric and phenotypic changes in blood pDC are occurring during allergen-specific immunotherapy [ 63 ]. These findings are in line with the observation of a decrease of circulating pDC and phenotypic changes in patients with HDM allergy during subcutaneous immunotherapy [ 64 ]. Furthermore, it has been described that pDC are generally critical for tolerance induction by inducing Treg cells in a mouse model for uptake and presentation of oral allergen OVA [ 65 ].…”
Section: Discussionsupporting
confidence: 89%
“…Unfortunately, in the present study, neither bilateral EVN nor SCIT increased the serum IFN-γ levels of the AR patients within 1 year after treatment. AIT is also expected to downregulate the inflammatory cytokines and chemokines [29, 30]. Our data showed that SCIT could reduce IL-4 and TNF-α levels in the peripheral blood, and these players may participate in the intrinsic mechanism of immunotherapy for AR.…”
Section: Discussionmentioning
confidence: 72%
“…One key result is the involvement of innate immune pathways associated with dendritic cells, monocytes/macrophages and mast cells. Due to their location in mucous membranes, skin, respiratory tract and blood, they encounter allergens first‐line initiating and augmenting consequent immune responses 13,52‐54 . Antigen‐presenting cells (APC), especially DCs, play a pivotal role during the sensitization and elicitation phase by propagation of Th2‐biased immune responses 55 .…”
Section: Discussionmentioning
confidence: 99%